Analisis Determinan Kejadian Peningkatan Tekanan Darah pada Siswa-Siswi di Sekolah Menengah Wilayah Jakarta Selatan: Determinant Analysis of Elevated Blood Pressure among Secondary School Students in South Jakarta - Iin Fatmawati; Firlia Ayu Arini; Utami Wahyuningsih; Cumayo Putri Riode; Mediana Puji Larasati (Amerta Nutrition, 2025)
Background: Elevated blood pressure in adolescence is an early indicator of future risk for hypertension and cardiovascular disease in adulthood, with contributing factors including central adiposity, excess body fat, dietary patterns, and sedentary behaviour. The 2023 Indonesian Health Survey reported that 29.5% of the population aged ≥15 years in Jakarta had hypertension, highlighting the urgency of early-life interventions to reduce the future burden of chronic disease. Objectives: To analyze determinants associated with elevated blood pressure among secondary school students in South Jakarta. Methods: This study employed a quantitative approach with cross-sectional design. A total of 350 students were selected using stratified random sampling from two secondary schools in South Jakarta. Data collection encompassed structured assessments of participant characteristics, the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), the Adolescent Sedentary Activity Questionnaire (ASAQ), and anthropometric measurements. Data analysis was performed using Chi-Square test and logistic regression analysis. Results: Significant associations were observed between elevated blood pressure and waist circumference (p-value<0.001), body fat percentage (p-value<0.001), and sedentary behavior (p-value=0.004). In contrast, dietary fat intake was not significantly associated with elevated blood pressure (p-value=0.865). Multivariate analysis demonstrated that students with high waist circumference had a 3.7-fold higher risk of elevated blood pressure (95% CI=2.040–6.870) compared with those with a normal waist circumference. Conclusions: This study identifies waist circumference as the primary determinant associated with elevated blood pressure among secondary school students in South Jakarta. As a key indicator of central obesity, routine monitoring of waist circumference among adolescents is recommended as a preventive strategy to reduce the risk of elevated blood pressure and hypertension.